2017
DOI: 10.3847/2515-5172/aa9d2a
|View full text |Cite
|
Sign up to set email alerts
|

New or Improved Orbital Periods of Cataclysmic Binaries

Abstract: Wilder Laboratory Hanover, NH 1. EXPLANATION Cataclysmic variables (CVs) are close binary star systems in which a white dwarf accretes mass from a low-mass companion via Roche-lobe overflow. Warner (1995) presents a comprehensive review.The most significant observable number for a CV is its orbital period P orb . We report here CV orbital periods measured over the last several decades using the Hiltner 2.4m and McGraw-Hill 1.3m telescopes at MDM Observatory on Kitt Peak, Arizona, mostly with radial-velocity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Precise P orb measurements for an additional 23 systems (and updated measurements for a handful from the original sample) have since become available, increasing the sample to 72 systems. Of the new systems, six are eclipsing systems with observations using ULTRA-CAM/ULTRASPEC, 10 are from Thorstensen et al (2015Thorstensen et al ( , 2017 and the remaining seven are from the Ritter & Kolb (2003) catalogue (v7.24; see references within). All systems were discovered by the SDSS (e.g.…”
Section: Reviewing the Properties Of The Period Spikementioning
confidence: 99%
“…Precise P orb measurements for an additional 23 systems (and updated measurements for a handful from the original sample) have since become available, increasing the sample to 72 systems. Of the new systems, six are eclipsing systems with observations using ULTRA-CAM/ULTRASPEC, 10 are from Thorstensen et al (2015Thorstensen et al ( , 2017 and the remaining seven are from the Ritter & Kolb (2003) catalogue (v7.24; see references within). All systems were discovered by the SDSS (e.g.…”
Section: Reviewing the Properties Of The Period Spikementioning
confidence: 99%
“…So, based on these variations, Dobrzycka et al (1998) concluded that LS Cam might be an IP. Additionally, from the analysis of emission-line radial velocity curves, Thorstensen et al (2017) confirmed the orbital period of LS Cam to be 3.417 h.…”
Section: Ls Cammentioning
confidence: 73%
“…An estimation of some system parameters of LS Cam can be obtained using the positive superhump excess ǫ + = (P +sh − P orb )/P orb and the negative superhump deficit ǫ − = (P −sh − P orb )/P orb . With the periods given in Table 1 and P orb = 0.1423853 ± 0.0000005 days (Thorstensen et al 2017), the values of ǫ + and ǫ − for LS Cam are 0.088 ± 0.007 and 0.034 ± 0.007 respectively. The excess and deficit are shown to correlate with the mass ratio (q) and the orbital period of the system (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other mentions of LS Cam in the literature include a work of Rodríguez-Gil (2005), where the binary is classified as a non-eclipsing SW Sex type system and a work of Thorstensen et al (2017), where an improved orbital period P orb = 0.1423853(5) days ≈ 3.42 hours is given.…”
Section: Introductionmentioning
confidence: 99%